2018
DOI: 10.1136/bmjopen-2017-019902
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenATP2B1andCACNB2polymorphisms and high blood pressure in a population of Lithuanian children and adolescents: a cross-sectional study

Abstract: ObjectivesRecently, genome-wide associated studies have identified several genetic loci that are associated with elevated blood pressure and could play a critical role in intracellular calcium homeostasis. The aim of this study was to assess the associations of ATP2B1 rs2681472 and CACNB2 rs12258967 gene polymorphisms with high blood pressure (HBP) among Lithuanian children and adolescents aged 12–15 years.Study design and participantsThis was a cross-sectional study of a randomly selected sample of 646 12–15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 68 publications
0
13
2
Order By: Relevance
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814, rs11014166, rs12258967) polymorphisms were associated with blood pressure and hypertension (no reports about CACNA1S polymorphisms), these SNPs were not consistent with our pre-experimental results (200 cases vs 200 controls, unpublished results). Therefore, based on the haplotype analysis results of the Beijing Han (Chinese Han in Beijing (CHB), HapMap) [18], we chose another 17 SNPs in the genes (CACNA1A, CACNA1C, CACNA1S, CACNB2) that encode the proteins of VDCCs to perform genotyping in the Dai population.…”
Section: Choosing Snps and Genotypingcontrasting
confidence: 72%
See 1 more Smart Citation
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814, rs11014166, rs12258967) polymorphisms were associated with blood pressure and hypertension (no reports about CACNA1S polymorphisms), these SNPs were not consistent with our pre-experimental results (200 cases vs 200 controls, unpublished results). Therefore, based on the haplotype analysis results of the Beijing Han (Chinese Han in Beijing (CHB), HapMap) [18], we chose another 17 SNPs in the genes (CACNA1A, CACNA1C, CACNA1S, CACNB2) that encode the proteins of VDCCs to perform genotyping in the Dai population.…”
Section: Choosing Snps and Genotypingcontrasting
confidence: 72%
“…Association analyses in China [14], Lithuanian [17] and Europe [16] have reported the association between CACNB2 polymorphisms (rs4373814 in Chinese Han, rs12258967 in Lithuanian and rs18748804 in Europe) and hypertension. In our study, we found three other positive SNPs (rs17539088, G minor , OR Dominant = 0.732 CI95% Dominant = 0.554-0.966, OR Additive = 0.769 CI95% Additive = 0.616-0.960; rs16917217, G minor , OR Dominant = 0.737 CI95% Dominant = 0.558-0.973, OR Additive = 0.776 CI95% Additive = 0.622-0.969; and rs61839222, A minor , OR Dominant = 0.737 CI95% Dominant = 0.558-0.973, OR Additive = 0.776 CI95% Additive = 0.622-0.969), which suggest a decreased risk, in CACNB2 after logistic regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814,…”
Section: Choosing Snps and Genotypingmentioning
confidence: 99%
“…Although the association analyses in the Chinese Han population [14,15] and other countries [16,17] suggested that the CACNA1A (rs8182538), CACNA1C (rs758116) and the CACNB2 (rs4373814, The sequencing images were transformed into sequenced reads through base recognition analysis, and final identification of SNPs was conducted by Samtools 0.1.19 [20].…”
Section: Choosing Snps and Genotypingmentioning
confidence: 99%
“…Kudryavtseva O et al [26]. investigated the effect of VDCCs on VSMC differentiation by injecting alpha Association analyses in China [14],Lithuanian [17]and Europe [16]have reported the association between CACNB2 polymorphisms (rs4373814 in Chinese Han, rs12258967 in Lithuanian and rs18748804 in Europe) and hypertension. In our study, we found three other positive SNPs (rs17539088, rs16917217 and rs61839222) in CACNB2 in a Dai population after logistic regression analyses.…”
Section: Logistic Regression Analysis Of Association With Hypertensionmentioning
confidence: 99%